STUDY OF THE METAMORPHIC EVOLUTION OF A CARBONATE-BEARING METAPERIDOTITE FROM THE SIDIRONERO COMPLEX (CENTRAL RHODOPE, GREECE) USING P-T AND P(T)-XCO2 PSEUDOSECTIONS - Mposkos, E.; Baziotis, I. (Bulletin of the Geological Society of Greece, 2010)
The carbonate-bearing metaperidotite from Sidironero Complex, north of the Xanthi town is composed primarily of olivine and orthopyroxene megacrysts and of Ti-clinohumite, tremolite, chlorite, dolomite, magnesite, talc, antigorite and spinel group minerals. The metaperidotite underwent a prograde HP metamorphism probably isofacial with the neighboring amphibolitized eclogites. Calculated P-T and P(T)-XCO2 phase diagram sections (pseudosections) for the bulk rock composition showed that XCO2 in the fluid phase was extremely low (≤0.008) at the first stages of the metamorphism and increased up to 0.022 at the peak P-T conditions ~1.5 GPa and 690 0C. The prograde metamorphism probably started from a hydrated and carbonated assemblage including talc+chlorite+magnesite+dolomite and proceeded with tremolite and antigorite formation before olivine growth, and orthopyroxene formation after olivine growth (Ol-1). Matrix dolomite, breakdown of chlorite (Chl-1) to Cr spinel+olivine and of Ti-clinohumite to olivine+Mg-ilmenite occurred during decompression. The P-T path is constrained by the absence of clinopyroxene in the metaperidotite.